Trend Analyses of Economical and Socio-Cultural Options of Arfak Tribe Pig Farmers on Shaping Pig Farming Development in Manokwari, West Papua-Indonesia - D.A. Iyai; Mulyadi .; B. Gobay (Department of Animal Sciences, Faculty of Agriculture, Sriwijaya University, Indonesia, 2015)
The multifunction of pigs for the Papuan are divergences and interelated. This study wasaimed to seek the objectives of keeping pigs by Arfak tribe and to find the trend relationships ofeconomical and socio-cultures components determining the development of pig farming inManokwari. A one-month field research was done at Manokwari Barat district. Quiztionaire was thetool used to record and collect the data. Snowball method was applied to chose the pig farmerparticipants and 60 respondents were participated. Several variables were quantified to measure thepercentages of socio-culture and economic objectives. The finding shown that income generation,savings barter were the subsequent components shaping the economic objectives and while organicfertilizer and biofertilizer resulted from manure were not applied yet. Although dung was frequentlyproduced and spreaded at the pig house and around backyard. Socio-culture was done in the meansof merrital prices, peaceness, gift and parties, respectively. The other findings were that thealternation of pig development indicated by herd size had positive relationship with the twomotives. Similar relationship was shown by number of aided farmers. Hence, the changes of pigfarming systems, e.g. extensive to semi-intensive and/or intensive to semi-intensive had shownweak relationship.Key words : Economical motive, social-culture motive, Arfak pig farmers, Manokwari